Konsep Dasar Islam Wasathiyah : (Menyoroti Islam Wasathiyah Berdasarkan Pandangan Para Ulama) - Uminatuz Zahro (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
The contemporary era is characterized by globalization which has had a tremendous impact on thoughts, behavior and even personalities which are very diverse and easily spread to remote corners of the country. Television and the internet are entering the alleys so that community groups are becoming more pluralistic both in mind and physically. Cultural diversity is often considered the wealth of a nation. However, religious diversity is often used as a concern for the harmony and pluralism of a nation. The dynamics of Indonesian Muslims are currently being shaken by the arrival of imported ideologies that are not in accordance with the characteristics of the Indonesian nation. We need to be wary of these new understandings because instead of having a good impact on society, these understandings actually destroy people's lives. Wasathiyah Islam emerged as a counterweight to the emergence of groups that often converted and infidelized other groups. The concept of Wasathiyah Islam or Islamic moderation has now become a direction or school of Islamic thought which has become an important discourse in the Islamic world today, seeing the condition of Muslims who are always accused in every incident of violence committed by Muslim individuals who do not understand the character and essence of the teachings. Islam. Muslim scholars are currently predicting religious moderation as a solution to this problem.